A prototype for converting and merging multi type databases to single database / Suzana Ahmad and Siti Zaleha Zainal Abidin - Ahmad, Suzana; Zainal Abidin, Siti Zaleha (Research Management Institute (RMI), 2013)
FSKM or Faculty of Computer and Mathematical Sciences is a well-known faculty in UiTM. FSKM has seven academic centres, which are Computer Science, Computer Technology and Networking, System Science, Mathematics, Statistics, Actuarial Science and Quantitative Methods. In keeping with the University’s mission and the Faculty’s mission, faculty administration has to manage a large number of data that was kept in different format and also different databases. Since these data are in different format and different databases, problems such as: manipulating wrong or contradictory data (two data sources giving two different information); delivering wrong information to the user, due to data inconsistency; increase workload leading to over budgeting; and delay in applications delivery with direct and/or indirect consequences on the activities of the faculty. Stand-alone databases are hard to maintain and to expand because there is a general lack of understanding of how the workflows and business rules are built into them. They are also difficult to integrate with newer systems in a modern platform because of non-extensibility, incapability and less openness of underlying hardware and software. These scenarios are not only happened in FSKM, but also common to other faculties throughout UiTM and other government agencies. This study is to investigate the advantages and disadvantages of converting stand-alone database to web-based database focusing on appropriateness, functionality, extensibility, scalability, challenges, data management and development tools. This research is to investigate the appropriateness, functionality, extensibility, scalability, challenges, data management and development tools of converting stand-alone database to webbased database. Research will also focuses on appropriateness, functionality, extensibility, scalability, challenges, data management and development tools of data conversion. Based from investigation of this research, a new conversion model for web-based database will be produced.